(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Irrational prescribing of medications is a major therapeutic issue in Bangladesh, which can result in various serious health complications. As prescriptions are essential for the rational use of medicines and play a vital role in disease treatment, this study sought to examine prescription patterns across different hospitals in Dhaka city, Bangladesh. Between July and December, 2024 a random sample of 400 prescriptions was collected from 4 (four) hospitals in Dhaka, Bangladesh. The data were analyzed using IBM SPSS (Statistical Package for the Social Sciences) and are displayed as frequencies, means, and percentages. The majority of patients were aged 21-40 years, with a balanced gender distribution. Commonly prescribed drugs included proton pump inhibitors, antibiotics, and respiratory agents, with Montelukast and Deflazacort being the top generics. Males received more analgesics and antibiotics, while females were prescribed more proton pump inhibitors and anti-diabetic drugs. Government institutions prescribed a broader range of medications, while non-government ones focused on specialized treatments. This study highlights that physicians’ prescribing practices significantly affect factors such as the frequency of doctor visits, medication choices, polypharmacy, rational antibiotic use, and gender biases. To improve health outcomes in Bangladesh, it is essential to establish rational prescribing guidelines and offer adequate training to healthcare professionals. Dhaka Univ. J. Pharm. Sci. 24(2): 187-196, 2025 (December)